Immunogenicity of Outer Membrane Proteins in a Lipopolysaccharide-Deficient Mutant of Neisseria meningitidis: Influence of Adjuvants on the Immune Response - Steeghs, Liana (American Society for Microbiology, 1999)
The immunogenicity of outer membrane complexes (OMCs) or heat-inactivated bacteria of a lipopolysaccharide (LPS)-deficient mutant derived from meningococcal strain H44/76 was studied. The immune response in BALB/c mice to the major outer membrane proteins was poor compared to the immune response elicited by wild-type immunogens. However, addition of external H44/76 LPS to mutant OMCs entirely restored the immune response. By using an LPS-deficient mutant, it may be possible to substitute a less toxic compound as adjuvant in meningococcal outer membrane vaccines. Therefore, a broad panel of adjuvants were tested for their potential to enhance the immunogenicity of LPS-deficient OMCs. AlPO(4), Rhodobacter sphaeroides LPS, monophosphoryl lipid A and alkali-hydrolyzed meningococcal LPS showed significantly lower adjuvant activity than did H44/76 LPS. Adjuvant activity similar to H44/76 LPS was found for Escherichia coli LPS, meningococcal icsB and rfaC LPS, QuilA, subfractions of QuilA, and MF59. Good adjuvant activity was also found with meningococcal htrB1 LPS, containing penta-acylated lipid A. Antisera elicited with the less active adjuvants showed relatively high immunoglobulin G1 (IgG1) titers, whereas strong adjuvants also induced high IgG2a and IgG2b responses in addition to IgG1. Antisera with the IgG2a and IgG2b isotypes showed high bactericidal activity, indicating that adjuvants promoting the IgG2a and IgG2b response contribute most to the protective mechanism. Thus, this study demonstrates that the immunogenicity of meningococcal LPS-deficient OMCs can be restored by using less toxic adjuvants, which opens up new avenues for development of vaccines against meningococcal disease.